INFLUENCE OF FAILURE-FREE OPERATION LEVEL ON COSTS RELATED TO PRODUCTION AND GUARANTEE SERVICE OF INNOVATIVE PRODUCTS - I. M. Ter-Saakova; N. I. Podalyakina; V. A. Khodakovsky (Научный вестник МГТУ ГА, 2018)
Basis of market of national consumption is presently formed by non-redundant products. Reliability of these devices is wholly determined by the level of failure-free operation of their constituents. With the industrial products of the non-domestic use redundancy both in the repaired and non-repaired equipment is used on different levels: redundancy at the level of components, blocks and units on the whole, and also at the level of elements (deep fractional redundancy).To make a forecast on the share of products that fail during operation, one can know the probability of failure-free operation of the product for a certain time. The article gives the indicator of the probability of failure-free operation of the product – a quantifiable estimated value, which is calculated as the ratio of the undisclosed number of products to their total number. The graph characterizing the changes in the probability of failure-free operation of the products is given. It is assumed that the probability of failure-free operation of articles varies exponentially. The construction of an economic model based on the category of fail-safe products is considered. This model is built taking into account the condition that the product guarantees issued by the manufacturer should be correlated with the number of possible failures of the products during this time. The conclusion is made that the product reliability category is the only category of risk assessment of the manufacturer on the market when issuing guarantees for its products. The assumption is made that the price of improving the reliability can be different and depends on many circumstances, but always increase of the product reliability is associated with an increase of its cost. The problem is solved, due to the fact that some of the products supplied by the manufacturer to the market will fail. Thus, it is necessary to know the proportion of failed products, which is determined by the quality of manufacture and reliability of the product put in the process of its design and production. The graph of the dependence of the total costs for the production and operation of innovative products on the probability of their trouble-free operation is given. The main advantages of the proposed economic model are formulated.